2003
DOI: 10.1016/s0378-1097(03)00449-x
|View full text |Cite
|
Sign up to set email alerts
|

A study on microbial diversity in different cultivars ofBrassica napusin relation to its wilt pathogen,Verticillium longisporum

Abstract: Oilseed rape (Brassica napus) is one of the major oilseed crops in the world but is vulnerable to attack by many pathogens and insect pests. In addition to the host plant genotype, micro-organisms present in the rhizosphere and within plant tissues affect the susceptibility to plant pathogens. While rapid progress has been achieved concerning the concept of plant resistance genes, information on the role of the microbial community in plant protection is less apparent. We have studied the endophytic bacterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 34 publications
7
77
0
4
Order By: Relevance
“…This close relationship between clinical and environmental strains implies that the environment can be a reservoir for opportunistic human pathogens, especially the rhizosphere, where the characteristics that make a bacterial strain an efficient plant growth promoter (e.g., antagonistic properties, colonization ability) could also make it a threatening human opportunistic pathogen (4). P. aeruginosa has been isolated from roots of different plants, such as oilseed rape, potato, and rice (17,27,38,55). However, few studies have specifically tested the abilities of these strains to act as root colonizers and plant growth promoters (13).…”
Section: Discussionmentioning
confidence: 99%
“…This close relationship between clinical and environmental strains implies that the environment can be a reservoir for opportunistic human pathogens, especially the rhizosphere, where the characteristics that make a bacterial strain an efficient plant growth promoter (e.g., antagonistic properties, colonization ability) could also make it a threatening human opportunistic pathogen (4). P. aeruginosa has been isolated from roots of different plants, such as oilseed rape, potato, and rice (17,27,38,55). However, few studies have specifically tested the abilities of these strains to act as root colonizers and plant growth promoters (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified different biotic and abiotic factors influencing the structural and functional diversity of bacterial communities: (i) the plant species or genotype, (ii) the plant development stage or vegetation time, (iii) colonization with pathogens as well as the physiological state of the plant, (iv) the quality of the soil, (v) crop rotation, (vi) treatment with pesticides or fertilizers, and (vii) the geographical region (12,14,16,20,26,27,29). However, relatively little is known about how these factors influence fungal communities in rhizosphere and bulk soil.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial metabolites may have an active role in resistance development by functioning as signals mediating cross-talk between the endophytes and their host (Graner et al, 2003). Since the endophytic actinomycetes were isolated from medicinal plant and that strains expected to produce a wide variety of antifungal and plant growth regulatory bioactive metabolites (Bredi, 1989;Franco and Cautinho, 1991), they can be exploited as novel sources of natural products and novel biocontrol agents as well.…”
Section: Discussionmentioning
confidence: 99%